Efektifitas Suplemen Daun Kelor Terhadap Peningkatan Kadar Hemoglobin Ibu Hamil - Nurjanah, Siti; Melisa, Melisa (Universitas Malahayati, 2023)
ABSTRACT The health of pregnant women is the most important thing in maintaining the perfection of the fetus they contain, many factors cause the health of pregnant women to be disrupted, one of which is balanced nutritional intake and a healthy lifestyle that is not maintained. During pregnancy, a mother experiences many changes including emotional, hormonal and physical changes. one of the changes that must be considered is the decrease in blood hemoglobin levels, hemoglobin is very important in supplying oxygen to the brain and heart. During the pregnancy phase, hemoglobin often decreases and this will be fatal if allowed to become chronic. However, there are still many pregnant women who are not aware of the importance of maintaining a balanced hemoglobin level so that the health of the baby in the womb is maintained. The purpose of this study was to determine the effectiveness of moringa leaf supplements on increasing hemoglobin levels in pregnant women. The method used in this research is pre-test and post-test. The data collection technique was through testing hemoglobin levels before and after consuming moringa leaf supplements. The results of the analysis showed that there was an effect of giving moringa leaf supplements to increasing hemoglobin levels in pregnant women. Keywords : Analysis, Moringa Leaf Supplements, Hemoglobin Levels ABSTRAK Kesehatan ibu hamil merupakan hal yang terpenting dalam menjaga kesempurnaan janin yang dikandung, banyak faktor penyebab kesehatan ibu hamil terganggu slah satunya asupan gizi seimbang dan pola hidup sehat yang kurang terjaga. Pada masa kehamilan seorang ibu banyak mengalami perubahan diantaranya perubahan emosional, hormone dan perubahan fisik. salah satu perubahan yang harus diperhatikan adalah menurunnya kadar hemoglobin darah, hemoglobin sangat penting dalam memasok oksigen menuju otak dan jantung. Pada fase kehamilan hemoglobin sering kali mengalami penurunan dan ini akan berakibat fatal jika dibiarkan sampai menjadi kronis. Namun masih banyak ibu hamil yang tidak menyadari akan pentingnya menjaga kadar hemoglobin tetap seimbang agar kesehatan bayi dalam kandungan terjaga. Tujuan penelitian ini untuk mengetahui efektifitas suplemen daun kelor terhadap peningkatan kadar hemoglobin pada ibu hamil. Metode yang digunakan pada penelitian ini adalah pre-test dan post-test. Teknik pengumpulan data melalui pengetesan kadar hemoglobin sebelum dan sesudah mengkonsumsi suplemen daun kelor. Hasil analisis menunjukkan bahwa terdapat pengaruh pemberian suplemen daun kelor terhadap peningkatan kadar hemoglobin pada ibu hamil. Kata Kunci : Analisis, Suplemen daun kelor, Kadar Hemoglobin